Antileishmanial Activity of 4,8-Dimethoxynaphthalenyl Chalcones on Leishmania amazonensis - Kaio Maciel de Santiago-Silva; Bruna Taciane da Silva Bortoleti; Laudicéa do Nascimento Oliveira; Fernanda Lima de Azevedo Maia; Joyce Cristina Castro; Ivete Conchon Costa; Danielle Bidóia Lazarin; James L. Wardell; Solange M. S. V. Wardell; Magaly Girão Albuquerque; Camilo Henrique da Silva Lima; Wander Rogério Pavanelli; et al. (MDPI AG, 2022)
Leishmaniasis is a neglected tropical disease caused by Leishmania species. Available therapeutic options have several limitations. The drive to develop new, more potent, and selective antileishmanial agents is thus a major goal. Herein we report the synthesis and the biological activity evaluation against promastigote and amastigote forms of Leishmania amazonensis of nine 4,8-dimethoxynaphthalenyl chalcones. Compound ((E)-1-(4,8-dimethoxynaphthalen-1-yl)-3-(4-nitrophenyl)prop-2-en-1-one), 4f, was the most promising with an IC50 = 3.3 ± 0.34 μM (promastigotes), a low cytotoxicity profile (CC50 = 372.9 ± 0.04 μM), and a high selectivity index (SI = 112.6). Furthermore, 4f induced several morphological and ultrastructural changes in the free promastigote forms, loss of plasma membrane integrity, and increased reactive oxygen species (ROS). An in silico analysis of drug-likeness and ADME parameters suggested high oral bioavailability and intestinal absorption. Compound 4f reduced the number of infected macrophages and the number of amastigotes per macrophage, with an IC50 value of 18.5 ± 1.19 μM. Molecular docking studies with targets, ARG and TR, showed that compound 4f had more hydrogen bond interactions with the ARG enzyme, indicating a more stable protein-ligand binding. These results suggest that 4,8-dimethoxynaphthalenyl chalcones are worthy of further study as potential antileishmanial drugs.